Edukasi Mencuci Tangan Dalam Upaya Pencegahan Virus Corona Melalui Video Tutorial Pada Mahasiswa berkebutuhan Khusus Di Pendidikan Tinggi - Budi, Setia; Nurhastuti, Nurhastuti; Utami, Iga Setia (Jurnal Pendidikan Kebutuhan Khusus, 2021)
ABSTRACTCorona virus is a virus transmitted by animals and humans that has been declared a world pandemic by WHO. Washing hands is the most common practice as a form of early prevention of transmission of the corona virus. Children with special needs are children who have abnormalities / deviations from the average condition of normal children, generally in terms of physical, mental and social behavior characteristics. The purpose of this study was to increase the knowledge and ability to wash hands in students with special needs. The activity was carried out on November 22, 2020. The method used in this study is lectures and discussions as well as the practice of washing hands through video conferencing accompanied by special delivery by a sign language interpreter. Participants in this activity totaled 14 Students with Special Needs. The results obtained were increased knowledge of students with special needs and the ability to practice washing hands properly.